2015
DOI: 10.31768/2312-8852.2015.37(3):187-191
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Cytotoxicity of Рhotoexcited Fullerene C60 and Cisplatin Combination Against D Rugresistant Leukemic Cells

Abstract: Aim: To evaluate the viability of leukemic cells sensitive (L1210S) and resistant (L1210R) to cisplatin, ROS production and free cytosolic Ca2+ concentration under treatment with cisplatin or its combination with photoexcited fullerene C60. Methods: Cell viability was assessed by the MTT reduction assay. Light-emitting diode lamp (2.45 J/сm2) was used for photoexcitation of intracellular accumulated fullerene C60. Free cytosolic calcium concentration ([Ca2+]i) and ROS production in cells were estimated with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Based on our previous experience, in vivo anticancer effects of C 60 fullerene and C 60 + Dox nanocomplexes are accompanied by the increase of macrophage oxygen-dependent cytotoxicity toward authologic tumor cells (Prylutska et al 2015 ). In addition, our previous results revealed direct toxic effects of C 60 fullerene and its nanocomplexes with anticancer drugs on transformed leukocytes including myelocytic cells (Panchuk et al 2015 ; Scharff et al 2008 ; Franskevych et al 2015 ).…”
Section: Introductionmentioning
confidence: 91%
“…Based on our previous experience, in vivo anticancer effects of C 60 fullerene and C 60 + Dox nanocomplexes are accompanied by the increase of macrophage oxygen-dependent cytotoxicity toward authologic tumor cells (Prylutska et al 2015 ). In addition, our previous results revealed direct toxic effects of C 60 fullerene and its nanocomplexes with anticancer drugs on transformed leukocytes including myelocytic cells (Panchuk et al 2015 ; Scharff et al 2008 ; Franskevych et al 2015 ).…”
Section: Introductionmentioning
confidence: 91%
“…As it was earlier shown by us, a substantial increase of [Ca 2+ ]cyt in leukemic cells was detected 3 h after combined treatment with photoexcited C 60 and cisplatin [21]. To investigate the possible reason of this event Ca 2+ liberation from intracellular stores into the cytosol of leukemic cells was examined.…”
Section: Resultsmentioning
confidence: 60%
“…The both cell lines were cultured in RPMI 1640 medium supplemented with 10% fetal bovine serum (FBS, Sigma-Aldrich, Germany), 50 μg/ml penicillin and 100 μg/ml streptomycin at 37 °C in a 5% CO 2 humidified atmosphere. Cisplatin in a range of 0.1-10 µg/ml was shown to decrease the viability of L1210 in a dose dependent manner up to 90% during 72 h incubation with no effect on L1210R cells [21].…”
Section: Methodsmentioning
confidence: 92%
See 1 more Smart Citation
“…In the previous studies, we confirmed fullerene C 60 nanoparticles penetration into leukemic L1210 cells and demonstrated photoinduced cytotoxicity of accumulated C 60 determined by ROS production. 21 The possibility to decrease substantially the viability of cisplatin-resistant L1210R cells by combined treatment with photoexcited C 60 fullerene and cisplatin was also shown, 22 but the mechanisms of this phenomenon still need further investigation.…”
Section: Introductionmentioning
confidence: 99%